MicroRNA‐203–mediated inhibition of doublecortin underpins cardioprotection conferred by sevoflurane in rats after myocardial ischaemia‐reperfusion injury. Issue 17 (11th August 2020) - Tan, Jian; Wu, Zhiguo; Liu, Jun; Zhang, Wenting; Yuan, Wanqiu; Peng, Hong
Abstract: Myocardial ischaemia‐reperfusion (I/R) injury is a serious illness with high morbidity and mortality. Mounting evidence indicates the utility of sevoflurane (SEV) in the treatment of myocardial I/R injury. This study aimed to explore the molecular mechanisms underlying the protective action of SEV against myocardial I/R injury. A rat model of myocardial I/R injury was established, and I/R rats were treated with different concentrations of SEV. MicroRNA‐203 (miR‐203) and doublecortin (DCX) expression levels were determined using reverse transcription‐quantitative polymerase chain reaction. Putative target relationship between miR‐203 and DCX was explored using dual‐luciferase reporter gene assay and RNA‐binding protein immunoprecipitation assay. Ischaemia‐reperfusion rats were treated with SEV, miR‐203 antagomir or sh‐DCX, followed by determination of oxidative stress‐ and inflammation‐related factor levels using nitrite and enzyme‐linked immunosorbent assays, and that of apoptosis‐related factors using Western blot analysis. The apoptotic rate of myocardial tissues was determined using TdT‐mediated dUTP‐biotin nick end labeling (TUNEL) staining, and the infract area was evaluated using triphenyltetrazolium chloride staining. The results showed miR‐203 was poorly expressed and DCX was highly expressed in myocardial tissues of I/R rats. Sevoflurane was found to elevate miR‐203, and miR‐203, in turn, could target and reduce DCX expression. Sevoflurane, miR‐203 overexpression or DCX silencing resulted in declined oxidative stress, inflammation, apoptosis and infarct area, ultimately alleviating myocardial I/R injury. Collectively, these findings showed that SEV‐activated miR‐203 exhibited suppressive effects on myocardial I/R injury in rats and highlighted the SEV/miR‐203/DCX axis as a promising therapeutic target for myocardial I/R injury management.